Using existing infrastructure as ground control points to support citizen science coastal UAS monitoring programs - Rabins, Lucas F.; Theuerkauf, Ethan J.; Bunting, Erin L. (Frontiers in Environmental Science, 2023)
Recent publications have described the ability of citizen scientists to conduct unoccupied aerial system (UAS) flights to collect data for coastal management. Ground control points (GCPs) can be collected to georeference these data, however collecting GCPs require expensive surveying equipment not accessible to citizen scientists. Instead, existing infrastructure can be used as naturally occurring GCPs (NGCPs), although availably of NGCP placement on such infrastructure differs from published best practices of GCP placement. This study therefore evaluates the achievable accuracy of sites georeferenced with NGCPs through an analysis of 20 diverse coastal sites. At most sites NGCPs produced horizontal and vertical root mean square errors (RMSE) less than 0.060 m which are similar to those obtained using traditional GCPs. To support future UAS citizen science coastal monitoring programs, an assessment to determine the optimal NGCP quantity and distribution was conducted for six coastal sites. Results revealed that generally at least seven NGCPs collected in the broadest distribution across the site will result in a horizontal and vertical RMSE less than 0.030 m and 0.075 m respectively. However, the relationship between these placement characteristics and RMSE was poor, indicating that georeferencing accuracy using NGCPs cannot be optimized solely through ideal quantity and distribution. The results of these studies highlight the value of NGCPs to support UAS citizen science coastal monitoring programs, however they also indicate a need for an initial accuracy assessment of sites surveyed with NGCPs at the onset of such programs.